2013
DOI: 10.1016/j.strusafe.2013.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability-based topology optimization of trusses with stochastic stiffness

Abstract: NOTICE: this is the author’s version of a work that was accepted for publication in Structural Safety. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Structural Safety, 43, ( July 2013) DOI:10.1016/j.strusafe.2013.02.003 This Article is brou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…truss elements vs continuum elements). For instance, while in the author's previous paper (Jalalpour et al 2013) the response was found to follow a Gumbel distribution for truss structures under uncorrelated nor mally distributed node location uncertainty, in the present work-a continuum structure under correlated lognormally distributed material uncertainties-the response follows a lognormal distribution. To find the appropriate distribu tion.…”
Section: Response Statisticsmentioning
confidence: 40%
See 2 more Smart Citations
“…truss elements vs continuum elements). For instance, while in the author's previous paper (Jalalpour et al 2013) the response was found to follow a Gumbel distribution for truss structures under uncorrelated nor mally distributed node location uncertainty, in the present work-a continuum structure under correlated lognormally distributed material uncertainties-the response follows a lognormal distribution. To find the appropriate distribu tion.…”
Section: Response Statisticsmentioning
confidence: 40%
“…where C is the covariance matrix of the basic random vari ables, and tr{•} is the trace operator. The variance of the compliance, obtained using a first order estimate of C, can be expressed as (Asadpoure et al 2011;Jalalpour et al 2013):…”
Section: Response Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…One key aspect of designs obtained by means of optimization is their extreme sensitivity to any change in the parameters considered during optimization. Thus, slight changes in the magnitude and/or direction of the loads or in the distribution of material properties can lead to large changes in the design or in the effective response of the optimized component.…”
Section: Introductionmentioning
confidence: 99%
“…In , using maximum allowable displacement as a failure mode and considering the applied load and Young's modulus as random variables, a minimum weight continuum structure is achieved with a decoupled RBDO approach. In , a single‐loop algorithm is proposed to obtain minimum‐volume truss structures with uncertainties in both nodal locations and members' Young's modulus using maximum allowable displacement as a failure mode. In , a comparison between the nested RBDO algorithm (double‐loop) and a sequential RBDO algorithm is performed in structural problems and in a heat conduction problem, where the same results are achieved.…”
Section: Introductionmentioning
confidence: 99%